Study of sand brick ratio 1:6 for partial replacement of sand with palm oil clinker (5%, 10%and 15%) - Nur Syahira, Che Mohd Nawi (2019)
Nowadays, the construction industry and environmental management system has experienced a rapid development. Unfortunately, the rapid development of construction industry and environmental management has led to environmental pollution and the increased of waste generation from various sources. The oil palm industry is one of the major industries in Malaysia. According Malaysia Palm Oil Board (MPOB, 2015), palm oil industry in Malaysia produces about 90 million tons of palm oil in year 2014. A massive number of production will results to the massive number of waste produced. One of the waste produced in the oil palm industry is palm oil clinker (POC).This research is to study on the use of palm oil clinker (POC) as partial replacement for fine aggregate in cement sand brick. This study will benefits on reducing the use of natural sand. The effect of using different percentages of POC to LWSB due to compressive strength was investigated. There are three series of mix formulation of cement sand brick with mix density of 1600 kg/m3 were prepared that comprise of 5%, 10%, 15% as partial sand replacement from the total volume of sand was replaced with POC. The outcomes from replacing POC has resulting a good strength as in per requirement in JKR standard.